The Manifestation of Ethical Laws In “Statutes of Timur” - Dosmurod Khudaykulov (Zien Journals, 2021)
The life experiences and philosophical views of Amir Temur, who is mentioned in history as a just ruler and a skilful commander, especially the study of the pandnoma "Temur's Statutes" in terms of historical truth, scientific study of its moral content are important in the development of Uzbek national philosophy. In addition, the scientific substantiation of the necessity and condition of the qualities of Amir Temur for the new generation, the study of the moral and spiritual heritage of our great ancestor, first of all, the moral views of Amir Temur, his great ruler and spiritual leader are important. In this sense, the moral philosophy of Amir Temur is based on the harmony of man - society - culture - spirituality.
Keywords: History; statutes; social life; personal ethics